Contributions to the study of a class of optimal control problems on the matrix lie group SO(3) - Rodgerson, Joanne Kelly (Rhodes University, Faculty of Science, Department of Mathematics, 2009)
The purpose of this thesis is to investigate a class of four left-invariant optimal control problems on the special orthogonal group SO(3). The set of all control-affine left-invariant control systems on SO(3) can, without loss, be reduced to a class of four typical controllable left-invariant control systems on SO(3) . The left-invariant optimal control problem on SO(3) involves finding a trajectory-control pair on SO (3), which minimizes a cost functional, and satisfies the given dynamical constraints and boundary conditions in a fixed time. The problem is lifted to the cotangent bundle T*SO(3) = SO(3) x so (3)* using the optimal Hamiltonian on so(3)*, where the maximum principle yields the optimal control. In a contribution to the study of this class of optimal control problems on SO(3), the extremal equations on so(3)* (ident ified with JR3) are integrated via elliptic functions to obtain explicit expressions for the solution curves in each typical case. The energy-Casimir method is used to give sufficient conditions for non-linear stability of the equilibrium states.,KMBT_363,Adobe Acrobat 9.54 Paper Capture Plug-in
Keywords: Matrix groups; Lie groups; Maximum principles (Mathematics); Elliptic functions; Extremal problems (Mathematics)